The pros and cons of drinking tea - Baolu Zhao (World Scientific Publishing, 2020)
Tea is the most frequently consumed beverage worldwide besides water. Generally, there are five most popular types of tea: green, white, black, Pu'er, and oolong. Tea possesses significant antioxidant, anti-inflammatory, antimicrobial, anticarcinogenic, antihypertensive, neuroprotective, and cholesterol-lowering properties. Several research investigations, epidemiological studies, and meta-analyses suggest that tea and its bioactive polyphenolic constituents have numerous beneficial effects on health, including the prevention of many diseases, such as cancer, diabetes, arthritis, cardiovascular disease, stroke, and obesity. Recently, there are many reports about the resistance of tea to COVID-19 virus on the Internet, which has attracted a lot of attention to tea drinking and the discussion about the pros and cons of tea drinking. Based on our research results and relevant reports form literatures, this review is intended to highlight the beneficial effects and possible side-effects associated with tea consumption, answer 10 questions and point out a few matters for attention.